Male attraction tο virgin females in the almond seed wasp, Eurytomα amygdali Enderlein (Hymenoptera, Eurytomidae) - Pittara, I.S.; Katsouannos Β.Ι. (ENTOMOLOGIA HELLENICA, 1985)
Laboratory observations showed that adults of the almond seed wasp, Eurytoma amygdali Enderlein (Hymenoptera: Eurytomidae) were sexually mature on the first day of emergence. Experiments with an olfactometer showed that 1 to 12 day-old virgin females attracted the males. This attraction was found to be due to an odor, apparently a pheromone, released by the virgin females. The responsiveness of the males was higher the first part of the photophase. Under field conditions too, virgin females were attractive to males. “Delta” traps, containing 5-20 virgin females, suspended on almond trees, attracted and captured males released among the same trees. On the contrary, traps containing mated females or empty cages were not attractive to males.